The tritrophic system of the ambrosia gall of Neolasioptera tridentifera (Diptera: Cecidomyiidae) on Heliotropium curassavicum (Boraginales: Heliotropiaceae): fungal, inducer and gall aspects (Semiárida, 2025)
The cecidomyiid dipteran Neolasioptera tridentifera Kieffer & Jörgensen (Cecidomyiinae: Alycaulini) develops galls on the stems of heliotrope Heliotropium curassavicum L. (Boraginales: Heliotropiaceae). In field inspections, fungal mycelium was found together with the inducer inside the larval chamber of the galls. In this work, the morphological aspects of mature gall, the inducer's life strategy, and a first approach to the identification of mycelium are examined. The study was conducted on galls collected in Laguna Don Tomás, Santa Rosa, La Pampa. The anatomy of the gall was examined using microscopic preparations. In each season of the year, field inspections of the plants were carried out and gall dissections were carried out to investigate the life strategy. The study of the fungal mycelium was performed on samples extracted from the interior of the gall. The stem gall is fusiform and globoid, generally unilarval; the tunnel-like larval chamber develops in the parenchymal medulla, and the wall of the chamber is lined with fungal mycelium. The most abundant fungus obtained is a species of the genus Botryosphaeria (Dothideomycetes: Ascomycota). In the study area, the aerial parts of heliotrope plants die with frost and the galls remain attached to the plant, above the soil surface and half-buried, with third-instar larva inside. According to this, the inducer’s life strategy is type IB. In this work, it is reported for the first time that Neolasioptera tridentifera induces an ambrosia gall on Heliotropium curassavicum, and the presence of an associated fungal community is recorded, with a species of the genus Botryosphaeria being the most frequent.
Keywords: heliotrope; insect gall; life strategy; fungi; Botryosphaeria